High-entropy alloys catalyzing polymeric transformation of water pollutants with remarkably improved electron utilization efficiency - Ziwei Yao; Yidi Chen; Xiaodan Wang; Kunsheng Hu; Shiying Ren; Jinqiang Zhang; Zhao Song; Nanqi Ren; Xiaoguang Duan (Nature Communications)
Abstract High-entropy alloy nanoparticles (HEA-NPs) exhibit favorable properties in catalytic processes, as their multi-metallic sites ensure both high intrinsic activity and atomic efficiency. However, controlled synthesis of uniform multi-metallic ensembles at the atomic level remains challenging. This study successfully loads HEA-NPs onto a nitrogen-doped carbon carrier (HEAs) and pioneers the application in peroxymonosulfate (PMS) activation to drive Fenton-like oxidation. The HEAs-PMS system achieves ultrafast pollutant removal across a wide pH range with strong resistance to real-world water interferences. Furthermore, the nonradical HEAs-PMS system selectively transforms phenolics into high-molecular-weight products via a polymerization pathway. The unique non-mineralization regime remarkably reduces PMS consumption and achieves a high electron utilization efficiency of up to 213.4%. Further DFT calculations and experimental analysis reveal that Fe and Co in HEA-NPs act as the primary catalytic sites to complex with PMS for activation, while Ni, Cu, and Pd serve as charge mediators to facilitate electron transfer. The resulting PMS* complexes on HEAs possess a high redox potential, which drives spatially separated phenol oxidation on nitrogen-doped graphene support to form phenoxyl radicals, subsequently triggering the formation of high-molecule polymeric products via polymerization reactions. This study offers engineered HEAs catalysts for water treatment with low oxidant consumption and emissions.